Medication adherence in patients with mental illness and recent homelessness: contributing factors and perceptions on mobile technology use. (26th February 2020) - Watson, Tyler; Schindel, Theresa J; Simpson, Scot H; Hughes, Christine A
Abstract: Objectives: The primary objective was to determine medication-taking behaviours and factors influencing adherence in patients with mental illness and recent homelessness. Secondary objectives were to explore patients' perceptions on mobile technology use to support adherence. Methods: A constructivist approach and qualitative description method was used. The sample population consisted of patients with recent homelessness and mental illness affiliated with a community-based outreach programme in Canada. Participants were purposefully selected; semi-structured interviews were conducted to elicit information on medication-taking strategies and mobile technology to support adherence. A standardized questionnaire collected demographic and medical information; the Medication Adherence Rating Scale (MARS) was used to evaluate self-reported adherence. Questionnaire data were analysed using summary descriptive statistics. Interview data were subject to qualitative content analysis. Key findings: Fifteen participants with a mean age of 44 years were included. The mean MARS score ± standard deviation was 7.3 ± 1.5. Themes arising from the data included patient factors (i.e. insight, attitudes towards medications, coping strategies) and external factors (i.e. therapeutic alliance, family support that impacted adherence) and technology use and health. Eight participants (53%) had access to a mobile phone. There was a moderate interest in the use of mobile technology to support adherence, with cost and technology literacy identified as barriers. Conclusion: External supports and individual medication management strategies were important in supporting medication adherence in this patient group. Perceived need for mobile technology, in addition to existing supports for adherence, was not high. Challenges accessing and maintaining consistent mobile technology and individual preferences should be considered when developing mobile technology-based interventions.